Karakteristik Hunian Buruh Berpenghasilan Rendah: Pondok Boro Kampung Sumeneban Semarang - Fika Annisa' Sholihah; Ardhya Nareswari (Arsir: Jurnal Arsitektur, 2024)
One of the problems in urban areas is the increasing need for housing. This happens in various metropolitan cities, one of which is Semarang as the 5th largest city in Indonesia. With housing needs, especially for low-income workers, Pondok Boro is a solution for them. The aim of this research was to determine the residential characteristics of Pondok Boro Kampung Sumeneban, Semarang. The method used is descriptive qualitative, using purposive sampling. From the results of the discussion, the residents' priority scale does not concern the quality of housing, the most important thing for them is a cheap rental system, and being close to their place of work makes Pondok Boro a choice for workers who migrate to the city of Semarang. With the ownership status of the residence being managed by a private party, this building still has not had much repair or residential development. From the physical aspect of the building, there is a change in the function of the building, which was originally a warehouse into a residence for low-income workers which has two types, namely the stall type and the room type. From a macro perspective, the building still uses original materials, only a few materials such as roof tiles and additional space that adapt to the residents' needs.